1997
DOI: 10.1080/01448765.1997.9755179
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Management History and the Role of Plant Mineral Balance as a Determinant of Maize Susceptibility to the European Corn Borer

Abstract: Proponents of organic fanning have long suggested that their methods produce "healthy" crops that are less susceptible to insects and diseases. Experimental comparisons of European corn borer (ECB) egg-laying response to maize plants grown in a greenhouse in soil collected from either organically or conventionally managed farms provided evidence consistent with these assertions. In each of three paired comparisons, higher egg-laying occurred on plants in conventional soil. Subsequent studies suggested that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…The differences could not have been attributed to the reduction in plant vigor in the absence of chemical fertilizers because we did not detect any difference in plant size or canopy cover, while yields were actually higher in manure-amended plots. Because natural enemy pressure on Colorado potato beetle populations in northern Maine is extremely limited, Alyokhin et al 2005 speculated that, in accordance with the mineral balance hypothesis (Phelan et al 1996, Phelan 1997, the observed response was plant-mediated. However, before this study, no direct evidence was available to show that growing on manure-amended soils indeed makes potato plants less suitable Colorado potato beetle hosts.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The differences could not have been attributed to the reduction in plant vigor in the absence of chemical fertilizers because we did not detect any difference in plant size or canopy cover, while yields were actually higher in manure-amended plots. Because natural enemy pressure on Colorado potato beetle populations in northern Maine is extremely limited, Alyokhin et al 2005 speculated that, in accordance with the mineral balance hypothesis (Phelan et al 1996, Phelan 1997, the observed response was plant-mediated. However, before this study, no direct evidence was available to show that growing on manure-amended soils indeed makes potato plants less suitable Colorado potato beetle hosts.…”
mentioning
confidence: 81%
“…Plants grown on organically managed soils fertilized with manure and compost have been shown to be less favorable hosts for phytophagous insects than plants grown on conventionally managed soils fertilized with synthetic fertilizers (Eigenbrode and Pimentel 1988, Phelan et al 1995, 1996. Phelan et al (1996) and Phelan (1997) suggested a hypothesis that the organic matter and microbial activity associated with organically managed soils afford a buffering capability to maintain nutrient balance in plants. An optimal nutrient balance results in both good plant growth and resistance to herbivory, while crops growing in soils without these biologically based buffering capabilities are more likely to take up either excess or insufÞcient levels of certain nutrients.…”
mentioning
confidence: 98%
“…In an attempt to explain differences in pest pressure between organic and conventional systems, Phelan et al (1996) and Phelan (1997) offered the "mineral balance hypothesis," which postulates that the organic matter and microbes associated with organically managed soils afford a buffering capability to maintain nutrient balance in plants. It is further suggested that an optimal nutrient balance results in both good plant growth and resistance to herbivory.…”
mentioning
confidence: 99%
“…Though ECBs preferentially oviposit on corn, they also respond to volatiles of, and will readily oviposit on, other plant species (Udayagiri and Mason 1995), which suggests that ECBs are responding to chemical conditions within their host plants that are not plant speciesspecific. Studies with corn plants have shown that not only does O. nubilalis oviposition rate change significantly in response to different fertilization practices (Phelan et al 1995), but also to mineral profiles within individual plants (Phelan et al 1996, Phelan 1997. This broad response to chemical composition of host plants makes O. nubilalis a good model organism, as well as an economically important one, in which to assess fertilization-mycorrhiza mediated oviposition response.…”
Section: Study Systemmentioning
confidence: 99%
“…Some herbivorous insect species have been shown to lay fewer eggs upon, or show reduced performance when feeding upon, crops grown with organic fertilizers as opposed to synthetic fertilizers (Phelan et al 1995, Morales et al 2001, Hsu et al 2009, Cardoza 2011. Also, plants that have been reared in organically managed soils can achieve a ratio of microminerals (Mg, Ca, Fe, Al, Mn, Cu, Zn) that may make them less susceptible to herbivorous insects (Phelan 1997).…”
Section: Introductionmentioning
confidence: 99%